The unembodied metaphor: comprehension and production of tactile metaphors without somatosensation - Phillips, Jacob B.; Grenoble, Lenore A.; Mason, Peggy (Frontiers in Communication, 2023)
Proposals for embodied metaphor and embodied cognition have suggested abstract concepts are understood indirectly through the simulation of previous sensory experiences in a different domain. While exceptions have been observed for sensory deficits and impairments that are common, like vision and audition, it is commonly assumed that somatosensation (proprioception, haptic touch, pain, pressure, temperature, etc.) is fundamental for the comprehension of production of sensory metaphors and much abstract thought in general. In this way, our past sensory experiences are critical to our understanding not just of the world around us, but also of our sense of selves. This would suggest that Kim, who was born without somatosensation, would have difficulty understanding, using, or even thinking about many abstract concepts typically linked to different sensory experiences through metaphor, including a creation of a sense of self. In this paper, we report the results of a simple multiple choice survey in which individuals were asked to select the best sensory expression given the context. We find that Kim performs as well as controls despite lacking any previous direct sensory experiences of these concepts. We then turn to an examination of her spontaneous speech, highlighting that Kim uses tactile expressions in both their concrete sensory meaning and in abstract metaphors. Taken together, these two studies demonstrate that what is lost in sensory experiences can be made up in linguistic experiences, as Kim's understanding of tactile words was acquired in the complete absence of somatosensory experiences. This study demonstrates that individuals can comprehend and use tactile language and metaphor without recruiting past somatosensory experiences and thus challenges a strong definition of embodied cognition which requires sensory simulations in language comprehension and abstract thought.